Impact of HR Practices on Organizational Citizenship Behavior and Turnover Intentions - MUHAMMAD ATIQ RAFIQUE KHATTAK; MUHAMMAD ATIQ RAFIQUE KHATTAK; MADIHA KHAN; SHAHZAD KHAN; DR. DAUD ALI (Journal of Business & Tourism, 2021)
In 21st century, human resource is major and most valuable asset of organization. Human resource is one of the major tool for organization that will help to achieve competitive advantage in the age of competition. Without a good human resource, companies cannot establish a good team of professional for their jobs. Great human asset should have such qualities as high satisfaction with their employments, high responsibility towards the organization, high inspiration to serve general society and solid aims to work for the association eagerly and dependably. Organization can upgrade inside capacities to manage present or future difficulties to be looked by an organization through great Human Resource practices. Human Resource Practices is a hierarchical capacity assume a critical part in overseeing workforce through it proactive approach in lessening disparities and also to draw in, create, hold and propel workforces. In that capacity, when organization energizes value and decency, their representatives is anticipated to wind up more dedicated in their activity & job. In the field of HRM, employee turnover is a major problem. Employee turnover is a cause for concern when the best and efficient employees intend to switch towards another organization, and there may be something that organization could do to retain those employees. Most of the Telecom sector in Pakistan faces a serious problem of high employee turnover. Now employees are considered as a main source to achievement of competitive advantage and organizations should give more focus in order to compete in the market with competitors. Organizations higher performance will depend on their incomparable employees; employees would not only adequately perform their required job but exert efforts that are beyond necessities. Employee turnover expectation is the huge reason that gives guidance to hold the specific conduct. This investigation is investigating the effect of HR practices on representative turnover and OCB in Telecom part of Pakistan that is Warid and Mobilink. This exploration will add to the group of writing relating HR practices and effect of HR practices on representative turnover and OCB, in hypothetical casing work will depict the measurements of HR practices for estimation worker turnover aims and OCB. The examination will clarify of how HR rehearses influences worker maintenance and OCB in telecom associations of Pakistan. The investigation will inspect through experimental discoveries in which including descriptive examinations, and regression for finding the effect of HR hones on representative turnover and OCB. Data will be collected using standardized questionnaire administered. Data collected from the sample size of one hundred and fifty people. In this study one hundred and fifty questionnaires were distributed only eighty was returned included in sample size in which forty employees and forty supervisors are included from both the company.